2006
DOI: 10.1038/sj.leu.2404434
|View full text |Cite
|
Sign up to set email alerts
|

High efficacy and safety profile of fractionated doses of Mylotarg as induction therapy in patients with relapsed acute myeloblastic leukemia: a prospective study of the alfa group

Abstract: Pivotal phase II studies in acute myeloblastic leukemia (AML) patients in first relapse have used gemtuzumab ozogamicin (GO) (Mylotarg) at a dose of 9 mg/m 2 on days 1 and 14. These studies showed a 26% response rate (13% complete remission (CR) and 13% CRp (complete remission with incomplete platelet recovery)) but with high degree of hematological and liver toxicities. Based on in vitro studies showing a re-expression of CD33 antigenic sites on the cell surface of blasts cells after exposure to GO, we hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
167
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(179 citation statements)
references
References 19 publications
10
167
1
1
Order By: Relevance
“…Both, the median time to recovery of ANC >0.5 3 10 9 /L and blood platelets >50 3 10 9 /L was 27 days and thus comparable to literature data [10,19,26]. During myelosuppression, in almost all patients (88%) neutropenic fever emerged and four patients (17%) subsequently died due to infectious complications.…”
Section: Subsequent Treatmentsupporting
confidence: 87%
See 1 more Smart Citation
“…Both, the median time to recovery of ANC >0.5 3 10 9 /L and blood platelets >50 3 10 9 /L was 27 days and thus comparable to literature data [10,19,26]. During myelosuppression, in almost all patients (88%) neutropenic fever emerged and four patients (17%) subsequently died due to infectious complications.…”
Section: Subsequent Treatmentsupporting
confidence: 87%
“…In the literature, many studies on GO-based therapies have been reported. Using GO as a single agent therapy in patients with refractory or relapsed AML, CR was achieved in 13-26%, leading to a median OS of 4.9 to 12 months [10,21,[25][26][27]. As a single agent, GO more likely induced a second CR than high dose araC especially in older patients with early relapse [28].…”
Section: Subsequent Treatmentmentioning
confidence: 99%
“…GO at 3 mg/m 2 given on Days 1, 4 and 7) has been pioneered by the French ALFA group and revealed a favorable efficacy/toxicity profile. [22][23][24] For example, among 57 patients with AML in first relapse, GO monotherapy given in fractionated doses resulted in 15 (26%) CRs and 4 (7%) CRs with incomplete platelet recovery (CRps). Interestingly, relative to our study, the study by Taksin et al included adults of all ages requiring therapy for AML in first relapse with a CR duration of at least three and up to 18 months, 22 i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The median RFS was 11 months in both the group of patients, CR and CRp. No major liver toxicities were observed and the authors concluded that GO administered in fractioned doses showed an excellent efficacy/safety profile (Taksin et al, 2007).…”
Section: Go As Monotherapymentioning
confidence: 96%